Evaluasi Pelayanan TI di RSIA Bunda Arif Menggunakan IT Infrastructure Library - Nita Purnamasari; Zulia Karini; Retno Waluyo (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
The hospital is a center of health services for people who are required to perform their duties and functions better and improve the quality and comfort in the services provided, the hospital is also required to follow technological developments to improve existing performance. IT services used are expected to be able to support and fulfill the purpose of RSIA Bunda Arif so as to determine alignment and service for IT implementation, an evaluation is needed to assess whether the existing services are in line with organizational goals or not, given that information technology investments are not cheap. In this study, the framework that will be used in the evaluation of information technology services is to use the Information Technology Infrastructure Library Version 3 framework with the domain service operation. The results of the measurement of maturity level at RSIA Bunda Arif were carried out by giving questionnaires related to the chosen domain to 10 respondents, the value of the statement made based on the Likert scale. The results of the maturity level values ??obtained for each process are event management getting level 3, incident management getting level 2, problem management getting level 2, requesting fullfilment getting level 3, and access management getting level 4